2003
DOI: 10.1038/sj.onc.1206850
|View full text |Cite
|
Sign up to set email alerts
|

MBD4 deficiency reduces the apoptotic response to DNA-damaging agents in the murine small intestine

Abstract: MBD4 was originally identified through its methyl binding domain, but has more recently been characterized as a thymine DNA glycosylase that interacts with the mismatch repair (MMR) protein MLH1. In vivo, MBD4 functions to reduce the mutability of methyl-CpG sites in the genome and mice deticient in MBD4 show increased intestinal tumorigenesis on an Apc Min/ þ background. As MLH1 and other MMR proteins have been functionally linked to apoptosis, we asked whether MBD4 also plays a role in mediating the apoptoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
69
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 27 publications
3
69
0
1
Order By: Relevance
“…Interestingly, recent reports indicate that deficiencies in DNA repair pathways confer cellular resistance to fluoropyrimidines, [38][39][40][41] suggesting that this class of drugs has effects at the level of DNA. Such effects likely derive from perturbation of nucleotide pools, misincorporation of nucleotides during DNA replication and/or repair, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent reports indicate that deficiencies in DNA repair pathways confer cellular resistance to fluoropyrimidines, [38][39][40][41] suggesting that this class of drugs has effects at the level of DNA. Such effects likely derive from perturbation of nucleotide pools, misincorporation of nucleotides during DNA replication and/or repair, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…MBD4 has been shown in vitro to excise mismatched thymine (T) bases from oligo templates Petronzelli et al, 2000a, b), and mouse knockout models have found that in the absence of Mbd4, mutation frequency (MF) in vivo increases, mainly at methyl-CpG sites (Millar et al, 2002;Wong et al, 2002). MBD4 can also bind to MLH1 and Fas-associated death domain (FADD) proteins Screaton et al, 2003), and the small intestine of Mbd4 À/À mice shows reduced apoptosis in response to a variety of DNA-damaging agents (Cortellino et al, 2003;Sansom et al, 2003;Screaton et al, 2003). Absence of Mbd4 in mice also increases tumorigenicity in the tumour-susceptible APC min background (Millar et al, 2002;Wong et al, 2002).…”
mentioning
confidence: 99%
“…38 Mbd4 was essential for the normal apoptotic programme following DNA damage and Mbd4 deficiency can confer increased long-term clonogenic survival in vivo. 39 Clarke suggested that this might be a result of interaction with the death molecule FADD. A possible mechanism might be that Mbd4 retains FADD within the nucleus until DNA damage is recognised, whereupon FADD is released.…”
Section: Cell Survival: the Ins And Outsmentioning
confidence: 99%